2022
DOI: 10.3389/fpls.2022.774241
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Tracheid Dimensions of Conifer Xylem Reveals Evidence of Adaptation to Environmental Conditions

Abstract: Globally distributed extant conifer species must adapt to various environmental conditions, which would be reflected in their xylem structure, especially in the tracheid characteristics of earlywood and latewood. With an anatomical trait dataset of 78 conifer species growing throughout China, an interspecific study within a phylogenetic context was conducted to quantify variance of tracheid dimensions and their response to climatic and soil conditions. There was a significant difference in tracheid diameter be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…Hydraulic conductivity is governed by the morphology, dimensions (particularly the diameter), and spatial arrangements of the conducting elements (vessels and tracheids) (Hacke et al, 2017; Tyree & Zimmermann, 2002). The diameter of conducting elements varies according to tree size (Olson et al, 2014), environmental gradients (Arenas‐Navarro et al, 2021; Zheng et al, 2022), and position within trees (Petit et al, 2008; Spicer & Gartner, 2001). The latter factor determines the pattern of accumulation of hydraulic resistance along tree height, thus influencing whole‐tree hydraulic conductivity, especially in large trees (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hydraulic conductivity is governed by the morphology, dimensions (particularly the diameter), and spatial arrangements of the conducting elements (vessels and tracheids) (Hacke et al, 2017; Tyree & Zimmermann, 2002). The diameter of conducting elements varies according to tree size (Olson et al, 2014), environmental gradients (Arenas‐Navarro et al, 2021; Zheng et al, 2022), and position within trees (Petit et al, 2008; Spicer & Gartner, 2001). The latter factor determines the pattern of accumulation of hydraulic resistance along tree height, thus influencing whole‐tree hydraulic conductivity, especially in large trees (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Earlywood and latewood differ, above all, in cell size [14]. In relation to that, Zheng et al [44] confirmed differences in tracheid diameter between earlywood and latewood. Longer latewood than earlywood tracheids were measured in this study.…”
Section: Discussionmentioning
confidence: 78%
“…There are significant differences between species in the shapes of scatter plots and in the location/density of earlywood and latewood clusters, reflecting the specific features of the anatomical structure. This variability reflects species-specific features with regards not only to tree size (height), but also to ecophysiological traits and species-specific adaptations to habitat conditions [46][47][48][49]. Taking into account the estimates of the threshold value k = 0.105-0.136 obtained in this work, we can conclude that the usage of one universal rigid threshold of k, as both interpretations of the Mork criterion suggest, quite often does not reflect the actual intra-seasonal variability of the anatomical structure in conifer wood.…”
Section: Discussionmentioning
confidence: 99%